لترقية قدرة الطلبة على فهم البلاغة بمعهد دار العلوم العصرى بندا آتشيه Giving Question and Getting Answer تطبيق أسلوب (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
Darul Ulum is one of the Islamic Boarding School which accentuated the learning of “Balaghah”. This lesson is taught for Second grade students of Senior High School. However, some students are difficult to understand the lesson when teachers explain the material, especially “Ilmu ma’ani” material.  The mentioned problem was caused by the ineffective and inappropriate methods used by the teachers in Arabic Language learning especially “Balaghah” learning. In accordance to that, this research is purposed to know the effect of applying learning model known as “Giving question and getting answer” toward the improvement of students’ ability to understand “Balaghah” for students of Darul Ulum Modern Boarding School, Banda Aceh. The research method used in this research was Pre- Experiment Method with One Group Pre Test Post Test model. The data collection method used in this research was test, pre test and also post test. The population in this research is all of X grader students at Darul Ulum Modern Boarding, Banda Aceh, with total 99 students. The research sample is students of class X/C with total 33 students. The result of the research showed that students’ response toward the implementation of “Giving Question and Getting Answer” learning model was very good. This was showed by the result of Rank Test with Asympt value Sig. (2-tailed) 0.000 which is smaller than 0.05. Therefore, the implementation of “Giving Question and Getting Answer” learning model is effective in improving the ability of understanding “Balaghah” lesson for Darul Ulum Modern Boarding School students, Banda Aceh.
Keywords: Balaghah; Giving Question and Getting Answer